Stent and method for manufacturing the same
Patent Information
- Application Number
- JP2024229098
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-10-31
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2040-10-30
Smart Images

Figure 2025041886000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a bioabsorbable stent for cerebral aneurysm and a method for producing the same. [Background technology]
[0002] A cerebral aneurysm is a swelling of a part of a cerebral artery. A lump is usually formed when a branch of a large blood vessel in the brain is pushed by cerebral blood flow and gradually swells. If a cerebral aneurysm ruptures, it will cause subarachnoid hemorrhage, making it a very frightening disease. To prevent subarachnoid hemorrhage, it is necessary to treat cerebral aneurysms before they rupture. Treatment can be surgical, either by opening the skull and clipping, or by endovascular treatment using a cerebral aneurysm stent.
[0003] Treatment using a cerebral aneurysm stent is as follows: A doctor inserts a tube into an artery at the base of the leg, guides it to the cerebral aneurysm, and deploys a flow diverter stent from a catheter so that it straddles the cerebral aneurysm and leaves the flow diverter stent in the blood vessel. This slows down the blood flow to the cerebral aneurysm, causing it to gradually become thrombosed. As the thrombus is absorbed, the cerebral aneurysm gradually shrinks, and eventually the cerebral aneurysm is cured. Patent Document 1 discloses a flow diverter stent made of a NiTi alloy as the above-mentioned stent for cerebral aneurysm.
[0004] The flow diverter stent is made of NiTi alloy, so it is not absorbed by the body even after the cerebral aneurysm is cured. Therefore, the stent remains in the blood vessels of the brain, which causes a large burden on the patient. In other words, if the stent remains in the blood vessels of the brain, the patient must continue to take medication to prevent side effects, which causes an extremely large burden on the patient.
[0005] Therefore, if a stent for cerebral aneurysms is placed in an artery in the brain and is made from a material that is absorbed by the body after the cerebral aneurysm is treated, the burden on the patient thereafter can be reduced. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2013-135794 A Summary of the Invention [Problem to be solved by the invention]
[0007] An object of one aspect of the present invention is to provide a stent for cerebral aneurysm that is formed of a material that is absorbed by the body. [Means for solving the problem]
[0008] Various aspects of the invention are as follows. [1] A stent that has self-expanding properties and is placed across a cerebral aneurysm by being pressed against the blood vessel wall, It is bioabsorbable, A stent characterized by being made of a magnesium alloy containing 90 atomic % or more of Mg or pure magnesium. [2] In paragraph [1] above: The stent is characterized in that it is composed of a tubular braided body woven with wire made of the magnesium alloy or pure magnesium, or is composed of the wire by cross-coiling, parallel coiling or coiling. [3] In paragraph [1] above: The stent is characterized in that it is composed of a tubular braided body woven with two or more types of wire material, including a wire material made of a magnesium alloy containing 90 atomic % or more of Mg or pure magnesium, and a wire material made of a magnesium alloy having a composition different from the magnesium alloy or the pure magnesium and containing 90 atomic % or more of Mg, or is composed of the two or more types of wire material by cross coiling, parallel coiling or coiling. [4] In paragraph [1] above: The stent is characterized in that it is composed of a tubular braided body woven with two or more types of wire material, including a wire material made of a magnesium alloy containing 90 atomic % or more of Mg or pure magnesium, and a wire material made of a material different from the magnesium alloy or pure magnesium, or is composed of the two or more types of wire material through cross coiling, parallel coiling or coiling. [5] In paragraph [4] above: A stent, wherein the material is one selected from the group consisting of bioabsorbable polymers, W, Ta, Pt and Au. [6] In any one of paragraphs [2] to [5] above, A stent characterized in that the cross-sectional shape of the wire is round, elliptical or rectangular, and the aspect ratio of the elliptical or rectangular wire is 1 or more and 5 or less. [7] In any one of paragraphs [2] to [6] above, The stent is a flow diverter stent or a coil embolization stent. [8] In paragraph [7] above: The flow diverter stent has a surface coverage of 30% or more (preferably 35% or more) and a number density of holes of 14 / mm 2 or more (preferably 15 pieces / mm 2 (or more), The coil embolization stent has a surface coverage of 5% or more (preferably 10% or more) and a number density of holes of 0.2 holes / mm 2 or more (preferably 0.4 pieces / mm 2 (or more), A stent characterized in that the angle formed between the wires in the braid is equal to or greater than 10° and equal to or less than 70°. [9] In paragraph [7] or [8] above, The flow diverter stent has a bioabsorption rate of 12 months or more and 36 months or less; The coil embolization stent is characterized in that its bioabsorption rate is from 1 month to 3 months.
[10] In paragraph [9] above: The stent is characterized in that the surface of the stent is subjected to a surface treatment or coating.
[11] In any one of paragraphs [7] to
[10] above, The stent is characterized in that the diameter of the stent is 2 to 6 mm, and the length of the stent is 10 to 50 mm.
[12] In any one of [1] to
[11] above, The term "self-expanding" refers to a stent characterized in that the outer diameter of the stent after expansion in air is 4 to 12 times larger than the outer diameter before expansion.
[13] In any one of [1] to
[12] above, The stent is characterized in that the magnesium alloy is an alloy having a crystal structure having an α-Mg phase or a long period stacking ordered structure phase.
[14] A method for manufacturing a stent that has self-expanding properties and is placed across a cerebral aneurysm by being pressed against a blood vessel wall, comprising: The method includes the step (a) of weaving a wire with a number of strands of 8 or more (preferably 16 or more), The wire is made of a magnesium alloy containing 90 atomic % or more of Mg or pure magnesium, and has a yield stress (0.2% proof stress) of 300 MPa or more (preferably 500 MPa or more) and a Young's modulus (modulus of longitudinal elasticity) of 50 GPa or less, A method for producing a stent, wherein the wire has a diameter of 100 μm or less (preferably 80 μm or less).
[15] In paragraph
[14] above: the stent is a flow diverter stent, The number of strokes is 24 or more (preferably 48 or more), A method for producing a stent, wherein the wire has a diameter of 50 μm or less (preferably 30 μm or less).
[16] In paragraph
[14] or
[15] above, A method for manufacturing a stent, comprising a step (b) of subjecting the wire to a surface treatment or coating prior to the step (a), or a step (c) of subjecting the stent to a surface treatment or coating after the step (a).
[17] In paragraph
[16] above: The step (b) is to perform a polymer bonding or polymer coating on the surface of the wire, or to perform a hydrofluoric acid treatment, an anodizing treatment, or a DLC film formation treatment on the surface of the wire, The method for producing a stent, wherein the step (c) comprises subjecting the stent to a hydrofluoric acid treatment, an anodizing treatment, or a DLC film formation treatment.
[18] In any one of paragraphs
[14] to
[17] above, The method includes a step (d) of producing the wire before the step (a), The step (d) includes the steps of: (e) rapidly solidifying a molten magnesium alloy containing 90 atomic % or more of Mg or pure magnesium to produce a plurality of rapidly solidified products; (f) filling and sealing the plurality of rapidly solidified products in a copper can to produce a billet, and extruding the billet to produce a solidified product; (g) extruding the solidified product to produce a magnesium alloy base material wire; and (h) drawing the magnesium alloy base material wire a plurality of times to produce a magnesium alloy wire having an α-Mg phase or a long period stacking ordered structure phase, A method for manufacturing a stent, characterized in that the inner surface of the can is subjected to a chrome coating treatment.
[0009] By applying one embodiment of the present invention, a stent for cerebral aneurysm formed of a material absorbable by the body can be provided. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a diagram showing a stent for cerebral aneurysm composed of a tubular braided body woven with wires according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a diagram showing a stent for cerebral aneurysm formed by coiling a wire according to one embodiment of the present invention. [Diagram 3] FIG. 1 is a diagram showing a stent for cerebral aneurysm formed by parallel coiling a wire according to one embodiment of the present invention. [Figure 4] FIG. 1 shows a stent for a flow diverter according to one embodiment of the present invention. [Diagram 5] FIG. 5 is a schematic diagram showing a state in which the flow diverter stent 20 shown in FIG. 4 is placed in a blood vessel 22 so as to straddle a cerebral aneurysm 21. [Figure 6] FIG. 1 shows a stent for coil embolization according to one embodiment of the present invention. [Figure 7] FIG. 7 is a schematic diagram showing a state in which the coil embolization stent 30 shown in FIG. 6 is placed in a blood vessel 32 so as to straddle a cerebral aneurysm 31. [Figure 8] FIG. 2 is a schematic diagram for explaining a method for producing a magnesium alloy wire according to one embodiment of the present invention. [Figure 9] 1 is a photograph (SEM photograph) showing the appearance of each of the wires of Sample 1, Sample 2, Sample 3, Sample 4, and Sample 5 according to Example 1. [Figure 10] FIG. 10 is a diagram showing the results of measuring the yield stress (0.2% proof stress) of each of the wires of Samples 1 to 5 shown in FIG. [Figure 11] FIG. 10 is a diagram showing the results of measuring the Young's modulus (modulus of longitudinal elasticity) of each of the wires of Samples 1 to 5 shown in FIG. [Figure 12] 1 is a photograph showing the appearance of a stent for cerebral aneurysm according to Example 2. [Figure 13] FIG. 1A is a graph showing the immersion time dependence of the corrosion rate in simulated body fluid for comparative samples 1 and 2, and FIG. 1B is a graph showing the immersion time dependence of the corrosion rate in simulated body fluid for the sample of Example 3 and comparative sample 1. [Figure 14] FIG. 1 is a diagram showing a stent for cerebral aneurysm formed by cross-coiling a wire according to one embodiment of the present invention. [Figure 15] 1 is a photograph showing the appearance of a stent for cerebral aneurysm according to Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. However, the present invention is not limited to the following description, and it will be easily understood by those skilled in the art that the form and details of the present invention can be modified in various ways without departing from the spirit and scope of the present invention. Therefore, the present invention should not be interpreted as being limited to the description of the embodiments shown below.
[0012] (Embodiment 1) FIG. 1 is a diagram showing a stent according to one embodiment of the present invention, which is composed of a tubular braided body made of woven wires. The stent 10 is used to treat cerebral aneurysms, and is placed by being pressed against the blood vessel wall due to its self-expanding properties. However, the "stent" in this specification is different from a general stent.
[0013] A typical stent is placed at a site of stenosis or obstruction to expand the site of the stenosis or obstruction and secure the lumen in order to treat diseases caused by the stenosis or obstruction of blood vessels or other body lumens (trachea, lymphatic vessels, ureter, etc.). Therefore, a typical stent expands at the site of stenosis or obstruction to increase its outer diameter while maintaining the lumen intact. However, the "stent" in this specification is placed in a cerebral artery that is not narrowed or blocked, in order to treat a cerebral aneurysm in which a part of the cerebral artery bulges like a lump. Therefore, it does not need to have the same expansion function as a general stent, and it is sufficient that the stent has self-expandability to the extent that it can be pressed against the vascular wall of the cerebral artery. It is sufficient that the stent has the effect of ensuring blood flow in the blood vessel in which it is placed and restricting the blood flow into the aneurysm. In addition, the self-expandability mentioned here means that the outer diameter of the stent after expansion in air is 4 to 12 times the outer diameter before expansion.
[0014] The stent 10 shown in Fig. 1 is composed of a cylindrical braided body made of a plurality of wires 11a, 11b made of a magnesium alloy having a bioabsorbable α-Mg phase or a long-period stacking ordered structure phase or pure magnesium. The stent 10 has a cylindrical body. Magnesium is preferable because it has excellent biocompatibility and is not harmful even if absorbed by the body during or after treatment. The magnesium alloy referred to here is an alloy containing 90 atomic % or more of Mg. Wires having two or more different compositions may be used for the multiple wires 11a, 11b constituting the stent 10. For example, magnesium alloys having two or more different compositions may be used, or pure magnesium and a magnesium alloy may be used.
[0015] The wires 11a and 11b constituting the stent 10 may be made of two or more types of wires, including wires made of magnesium alloy or pure magnesium and wires made of a material different from the wires. The different material may be a material selected from the group consisting of a bioabsorbable polymer, W, Ta, Pt, and Au. W, Ta, Pt, and Au are visible, and are useful for confirming the position of the stent when placing the stent in the blood vessel of the cerebral artery. In addition, in order to ensure visibility, markers (not shown) made of a material selected from the group consisting of W, Ta, Pt, and Au may be attached to both ends of the stent 10. The visibility here means that since a stent made of a magnesium alloy transmits X-rays, the position of the stent cannot be confirmed with an X-ray fluoroscopy device used in stent placement surgery, but by attaching wires or markers made of W, Ta, Pt, and Au, which do not transmit X-rays, to the stent, the position can be confirmed with an X-ray fluoroscopy device.
[0016] Examples of bioabsorbable polymers include polyglycolic acid (PGA), copolymer of glycolic acid and L-lactic acid (PGLA; Poly(glycolide-co-L-lactide), copolymer of glycolic acid and DL-lactic acid (PGDLLA: Poly(glycolide-co-DL-lactide), poly-L-lactic acid (PLLA: Poly-L-lactide), poly-D-lactic acid (PDLA: Poly-D-lactide), poly-DL-lactic acid (PDLLA: Poly-DL-lactide), and the like. The wires using bioabsorbable polymers can be produced by melt spinning, wet spinning, dry spinning, gel spinning or the like, and these wires may be appropriately strengthened by hot drawing, cold drawing, heat treatment or the like.
[0017] The angle 18 formed by the wires 11a and 11b is preferably 10° or more and 70° or less. The cross-sectional shape of the wires 11a and 11b may be round, elliptical, or rectangular, and the aspect ratio of the elliptical or rectangular wire is preferably 1 or more and 5 or less. The diameter of the stent 10 is preferably 2 to 6 mm, and the length of the stent 10 is preferably 10 to 50 mm. The wires 11a and 11b may be subjected to a surface treatment or coating. Specifically, the surfaces of the wires 11a and 11b may be subjected to a polymer bond or polymer coating, or the surfaces of the wires 11a and 11b may be subjected to a hydrofluoric acid treatment, anodizing treatment, or DLC (Diamond Like Carbon) film formation treatment. Oxides, fluorides, etc. may be formed on the surfaces of the wires 11a and 11b by the surface treatment. The stent 10 may be subjected to a surface treatment or coating. Specifically, the stent 10 may be subjected to a hydrofluoric acid treatment, anodizing treatment, or DLC film formation treatment. Oxides, fluorides, etc. may be formed on the surfaces of the stent 10 by the surface treatment.
[0018] DLC is preferable because it has excellent biocompatibility and is not harmful when absorbed by the body during or after treatment. By applying such a surface treatment or coating, it is possible to control the time when the stent 10 is absorbed by the body.
[0019] According to this embodiment, the stent 10 is fabricated from a tubular body formed of wires 11a, 11b made of a magnesium alloy having an α-Mg phase or a long-period stacking ordered structure phase or pure magnesium, so that a stent for cerebral aneurysm that is absorbed by the body can be realized.
[0020] In this embodiment, a stent for cerebral aneurysms having a tubular braided body woven with wire has been described. However, if the stent for cerebral aneurysms is bioabsorbable, it can be modified as follows.
[0021] 2 is configured by coiling a wire 13. That is, the stent 12 is in the form of a coil in which the wire 13 is wound in a circular or spiral shape.
[0022] 3 is constructed by parallel coiling wires 15 and 16. That is, this stent 14 is fabricated by arranging in parallel a coil of wire 15 wound circularly or spirally and a coil of wire 16 wound circularly or spirally. Also, three or more wires may be parallel coiled.
[0023] Also, the stent 19 for cerebral aneurysm shown in FIG. 14 is constructed by cross-coiling wires 17a and 17b. That is, the stent 19 is manufactured by overlapping a coil in which the wire 17a is wound circularly or spirally and a coil in which the wire 17b is wound circularly or spirally. It may also be cross-coiled with three or more wires. The multiple wires constituting the stents 14 and 19 may be wires made of two or more different compositions. For example, magnesium alloys of two or more different compositions may be used, or pure magnesium and magnesium alloys may be used. The multiple wires 15, 16, 17a, and 17b constituting the stents 14 and 19 may be wires made of two or more different types of wires, including wires made of magnesium alloys or pure magnesium and wires made of a material different from the wires. These stents 12, 14, and 19 are preferably applied to stents for coil embolization, which will be described later.
[0024] Another example of a stent for cerebral aneurysm (not shown) is manufactured through a process of processing a thin tube made of a magnesium alloy or pure magnesium from its outer periphery with a laser beam. The different material may be one selected from the group consisting of a bioabsorbable polymer, W, Ta, Pt, and Au. Note that W, Ta, Pt, and Au are visible, and are therefore useful for checking the position of a stent when placing the stent in a cerebral artery.
[0025] (Embodiment 2) FIG. 4 is a diagram showing a stent for a flow diverter according to one embodiment of the present invention. This flow diverter stent 20 is a stent for cerebral aneurysms, and is composed of a tubular braided body woven with 48 wires. The flow diverter stent 20 can be configured in the same manner as the stent 10 shown in Figure 1, except that the number of woven wires is greater than that of the stent 10 shown in Figure 1.
[0026] FIG. 5 is a schematic diagram showing a state in which the flow diverter stent 20 shown in FIG. A doctor guides a catheter into the skull via the femoral artery at the base of the leg, and the flow diverter stent 20 is inserted from the catheter into the blood vessel 22 so as to straddle the cerebral aneurysm 21, and is deployed in such a way that it presses against the vascular wall due to its self-expanding property. When the flow diverter stent 20 is placed in the parent blood vessel 22 in which the cerebral aneurysm 21 exists, the mesh structure on the surface of the flow diverter stent 20 restricts the blood flow (not shown) into the cerebral aneurysm 21, gradually promoting thrombosis inside and covering the neck part of the aneurysm 21 with the stent neointima, leading to complete occlusion of the cerebral aneurysm 21 after several months, and the flow diverter stent 20 itself gradually decomposes over the course of several months and finally disappears, leaving no foreign matter behind. However, if a non-bioabsorbable wire or the like is used in part of the flow diverter stent 20 to ensure visibility, it may not disappear and remain.
[0027] The flow diverter stent 20 has a surface coverage of 30% or more (preferably 35% or more) and a number density of holes of 14 / mm 2 or more (preferably 15 pieces / mm 2 The reason for this range is that the surface coverage is less than 30% or the hole density is less than 14 holes / mm 2If the thickness is less than this, even if the flow diverter stent 20 is deployed so as to straddle the cerebral aneurysm 21 as shown in FIG. 5, the effect of restricting the blood flow into the cerebral aneurysm 21 will be insufficient. The bioabsorption rate of the flow diverter stent 20 is preferably 12 months or more and 36 months or less, in order to keep the flow diverter stent 20 in the blood vessel 22 in which it is placed for the period from when the flow diverter stent 20 is placed in the parent blood vessel 22 in which the aneurysm 21 is present until the cerebral aneurysm 21 is completely occluded.
[0028] In this embodiment as well, the same effects as those in the first embodiment can be obtained.
[0029] (Embodiment 3) FIG. 6 is a diagram showing a stent for coil embolization according to one embodiment of the present invention. The coil embolization stent 30 is a stent for cerebral aneurysms, and is composed of a tubular braided body woven with 16 wires. The coil embolization stent 30 can be configured in the same manner as the flow diverter stent 20 shown in Fig. 4, except that it has fewer woven wires than the flow diverter stent 20 shown in Fig. 4. The cerebral aneurysm stent 10 shown in Fig. 1 can be used as both a flow diverter stent and a coil embolization stent.
[0030] FIG. 7 is a schematic diagram showing a state in which the coil embolization stent 30 shown in FIG. A doctor guides a catheter into the skull via the femoral artery at the base of the leg, and a coil embolization stent 30 is inserted from a thin treatment catheter through the catheter into a blood vessel 32 so as to cover the front and rear of the entrance of the cerebral aneurysm 31 firmly, and is deployed in a manner that presses against the blood vessel wall due to its self-expanding property. Then, a coil 33 is inserted into the cerebral aneurysm 31 from another thin treatment catheter through the catheter, and several coils are added until blood flow into the cerebral aneurysm 31 is almost completely stopped. The catheter is then removed. The coil 33 used here should preferably be a wire having the same bioabsorbability as the wire of the coil embolization stent 30.
[0031] In this manner, the coil embolization stent 30 is placed in the parent blood vessel 32 so as to cover the neck portion of the cerebral aneurysm 31, while the coil 33 is inserted into the cerebral aneurysm 31. This inhibits blood flow (not shown) into the cerebral aneurysm 31, gradually promoting internal thrombosis, and the neck portion of the cerebral aneurysm 31 is covered with the stent neointima, leading to complete occlusion of the cerebral aneurysm 31 after one to several months, and the coil embolization stent 30 and the coil 33 themselves are gradually decomposed over one to several months, and finally disappear, leaving no foreign matter behind. However, if a non-bioabsorbable wire or the like is used in part of the coil embolization stent 30 to ensure visibility, it may not disappear and may remain.
[0032] The coil embolization stent 30 has a surface coverage of 5% or more (preferably 10% or more) and a number density of holes of 0.2 / mm 2 or more (preferably 0.4 pieces / mm 2 The reason for this range is that the surface coverage is less than 5% or the hole density is less than 0.2 holes / mm 2 If the thickness is less than this, even if the coil embolization stent 30 is deployed so as to straddle the cerebral aneurysm 31 as shown in Figure 7, the coil 33 cannot be stably placed within the cerebral aneurysm 31, and the effect of suppressing the inflowing blood flow will be insufficient.
[0033] The rate of bioabsorption of the coil embolization stent 30 is preferably one month or more and three months or less, in order to keep the coil embolization stent 30 in the blood vessel 32 in which it is placed from the time when the coil 33 is placed in the cerebral aneurysm 31 while the coil embolization stent 30 is placed in the parent blood vessel 32 in which the cerebral aneurysm 31 is present until the cerebral aneurysm 31 is completely occluded.
[0034] In this embodiment as well, the same effects as those in the first embodiment can be obtained.
[0035] The magnesium alloy applied to the wire rod used in the first to third embodiments may be any one of the following alloys [1] to
[48] .
[0036] [1] The magnesium alloy is preferably an alloy containing a atomic % of Zn, b atomic % of Y, and the remainder being Mg and unavoidable impurities, where a and b satisfy the following (Formula 11) to (Formula 13) or (Formula 14) to (Formula 16), and has a crystal structure having an α-Mg phase or a long period stacking ordered structure phase. (Formula 11) 0.25≦a<5.0 (Formula 12)0.5 <b<5.0 (Formula 13)2 / 3a-5 / 6≦b (Formula 14)0.25≦a≦5.0 (Formula 15)0.5≦b≦5.0 (Formula 16)0.5a≦b [2] The magnesium alloy is preferably an alloy containing a atomic % of Zn, b atomic % of Y, and the remainder being Mg and unavoidable impurities, where a and b satisfy the following (Formula 11'), (Formula 12), and (Formula 13), and has a crystal structure having an α-Mg phase or a long period stacking ordered structure phase. (Formula 11')0.5≦a<5.0 (Formula 12)0.5 <b<5.0 (Formula 13)2 / 3a-5 / 6≦b [3] The magnesium alloy according to the above [1] or [2] may further contain at least one element selected from the group consisting of Yb, Tb, Sm, and Nd in a total amount of c atomic %, where c satisfies the following (Equation 17) and (Equation 18). (Formula 17)0≦c≦3.0 (Formula 18)0.1(0.2)≦b+c≦6.0 [4] The magnesium alloy according to the above [1] or [2] may further contain at least one element selected from the group consisting of La, Ce, Pr, Eu, Mm (misch metal), and Gd in a total amount of c atomic %, where c satisfies the following (Equation 19) and (Equation 20). (Formula 19)0≦c<2.0 (Formula 20)0.2≦b+c≦6.0 [5] The magnesium alloy according to the above [1] or [2] may further contain at least one element selected from the group consisting of La, Ce, Pr, Eu, Mm, and Gd in a total amount of c atomic %, where c satisfies the following (Equation 20) and (Equation 21). (Formula 20)0.2≦b+c≦6.0 (Formula 21)c / b≦1.5 [6] The magnesium alloy according to the above [1] or [2] may further contain at least one element selected from the group consisting of La, Ce, Pr, Eu, Mm, and Gd in a total amount of c atomic %, where c satisfies the following (Equation 22) and (Equation 23). (Formula 22)0≦c≦3.0 (Formula 23)0.1≦b+c≦6.0 [7] The magnesium alloy according to the above [1] or [2] may further contain at least one element selected from the group consisting of Yb, Tb, Sm, and Nd in a total of c atomic %, and at least one element selected from the group consisting of La, Ce, Pr, Eu, Mm, and Gd in a total of d atomic %, where c and d satisfy the following (Equation 14) to (Equation 16). (Formula 14)0≦c≦3.0 (Formula 15)0≦d<2.0 (Formula 16)0.2≦b+c+d≦6.0 [8] The magnesium alloy according to the above [1] or [2] may further contain c atomic % in total of at least one element selected from the group consisting of Yb, Tb, Sm, and Nd, and d atomic % in total of at least one element selected from the group consisting of La, Ce, Pr, Eu, Mm, and Gd, where c and d satisfy the following (Equation 16) and (Equation 17). (Formula 16)0.2≦b+c+d≦6.0 (Formula 17) d / b≦1.5 [9] The magnesium alloy according to the above [1] or [2] may further contain c atomic % in total of at least one element selected from the group consisting of Yb, Tb, Sm, and Nd, and d atomic % in total of at least one element selected from the group consisting of La, Ce, Pr, Eu, Mm, and Gd, where c and d satisfy the following (Equation 18) to (Equation 20). (Formula 18)0≦c≦3.0 (Formula 19)0≦d≦3.0 (Formula 20)0.1≦b+c+d≦6.0
[10] The magnesium alloy according to any one of [1] to [9] above may further contain more than 0 atomic % and not more than 2.5 atomic % in total of at least one element selected from the group consisting of Al, Th, Ca, Si, Mn, Zr, Ti, Hf, Nb, Ag, Sr, Sc, B, C, Sn, Au, Ba, Ge, Bi, Ga, In, Ir, Li, Pd, Sb, and V.
[11] The magnesium alloy may be an alloy containing a atomic % of Zn, a total of b atomic % of at least one element selected from the group consisting of Dy, Ho and Er, with the remainder being Mg and unavoidable impurities, where a and b satisfy the following (Equations 21) to (Equation 23) or (Equations 24) to (Equations 26), and the alloy has a crystalline structure having an α-Mg phase or a long period stacking ordered structure phase. (Formula 21)0.1≦a≦5.0 (Formula 22)0.1≦b≦5.0 (Formula 23)0.5a-0.5≦b (Formula 24)0.1≦a≦3.0 (Formula 25)0.1≦b≦5.0 (Formula 26)2a-3≦b
[12] The magnesium alloy may be an alloy containing a atomic % of Zn, a total of b atomic % of at least one element selected from the group consisting of Dy, Ho and Er, with the remainder being Mg and unavoidable impurities, where a and b satisfy the following (Formula 21'), (Formula 22'), and (Formula 23), or (Formula 24'), (Formula 25'), and (Formula 26), and has a crystalline structure having an α-Mg phase or a long period stacking ordered structure phase. (Formula 21')0.2≦a≦5.0 (Formula 22')0.2≦b≦5.0 (Formula 23)0.5a-0.5≦b (Formula 24')0.2≦a≦3.0 (Formula 25')0.2≦b≦5.0 (Formula 26)2a-3≦b
[13] The magnesium alloy according to the above
[11] or
[12] may further contain at least one element selected from the group consisting of Yb, Sm and Nd in a total amount of c atomic %, where c satisfies the following (Equation 27) and (Equation 28). (Formula 27)0≦c≦3.0 (Formula 28)0.1(0.2)≦b+c≦6.0
[14] The magnesium alloy according to the above
[11] or
[12] may further contain at least one element selected from the group consisting of La, Ce, Pr, Eu, and Mm in a total amount of c atomic %, where c satisfies the following (Equation 29) and (Equation 30). (Formula 29)0≦c≦3.0 (Formula 30)0.1(0.2)≦b+c≦6.0
[15] The magnesium alloy according to the above
[11] or
[12] may further contain at least one element selected from the group consisting of Yb, Sm, and Nd in a total of c atomic %, and at least one element selected from the group consisting of La, Ce, Pr, Eu, and Mm in a total of d atomic %, where c and d satisfy the following (Equation 31) to (Equation 33). (Formula 31)0≦c≦3.0 (Formula 32)0≦d≦3.0 (Formula 33)0.1(0.2)≦b+c+d≦6.0
[16] The magnesium alloy according to any one of the above
[11] to
[15] may further contain at least one of Y and Gd in a total of y atomic %, where y satisfies the following (Formula 34) and (Formula 35). (Formula 34)0≦y≦4.9 (Formula 35)0.1≦b+y≦5.0
[17] The magnesium alloy according to any one of
[11] to
[16] above may further contain more than 0 atomic % and not more than 2.5 atomic % in total of at least one element selected from the group consisting of Al, Th, Ca, Si, Mn, Zr, Ti, Hf, Nb, Ag, Sr, Sc, B, C, Sn, Au, Ba, Ge, Bi, Ga, In, Ir, Li, Pd, Sb, and V.
[18] At least a part of the long period stacking ordered structure phase of the magnesium alloy according to any one of the above
[11] to
[17] may be curved or bent.
[19] The magnesium alloy may be an alloy containing a atomic % of Zn, a total of b atomic % of at least one element selected from the group consisting of Gd, Tb, Tm and Lu, with the remainder being Mg and unavoidable impurities, where a and b satisfy the following (Formula 41) to (Formula 43) or (Formula 44) to (Formula 46), and the alloy has a crystalline structure having an α-Mg phase or a long period stacking ordered structure phase. (Formula 41)0.1≦a≦5.0 (Formula 42)0.25≦b≦5.0 (Formula 43)0.5a-0.5≦b (Formula 44)0.1≦a≦3.0 (Formula 45)0.25≦b≦5.0 (Formula 46)2a-3≦b
[20] The magnesium alloy may be an alloy containing a atomic % of Zn, a total of b atomic % of at least one element selected from the group consisting of Gd, Tb, Tm and Lu, with the remainder being Mg and unavoidable impurities, where a and b satisfy the following (Formula 41'), (Formula 42'), and (Formula 43), or (Formula 44'), (Formula 45'), and (Formula 46), and has a crystalline structure having an α-Mg phase or a long period stacking ordered structure phase. (Formula 41')0.2≦a≦5.0 (Formula 42')0.5≦b≦5.0 (Formula 43)0.5a-0.5≦b (Formula 44')0.2≦a≦3.0 (Formula 45')0.5≦b≦5.0 (Formula 46)2a-3≦b
[21] The magnesium alloy according to the above
[19] or
[20] may further contain at least one element selected from the group consisting of Yb, Sm and Nd in a total amount of c atomic %, where c satisfies the following (Equation 47) and (Equation 48). (Formula 47)0≦c≦3.0 (Formula 48)0.25(0.5)≦b+c≦6.0
[22] The magnesium alloy according to the above
[19] or
[20] may further contain at least one element selected from the group consisting of La, Ce, Pr, Eu, and Mm in a total amount of c atomic %, where c satisfies the following (Equation 49) and (Equation 50). (Formula 49)0≦c≦2.0 (Formula 50)0.25(0.5)≦b+c≦6.0
[23] The magnesium alloy according to the above
[19] or
[20] may further contain at least one element selected from the group consisting of Yb, Sm, and Nd in a total of c atomic %, and at least one element selected from the group consisting of La, Ce, Pr, Eu, and Mm in a total of d atomic %, where c and d satisfy the following (Equation 51) to (Equation 53). (Formula 51)0≦c≦3.0 (Formula 52)0≦d≦2.0 (Formula 53)0.25(0.5)≦b+c+d≦6.0
[24] The magnesium alloy according to any one of
[19] to
[23] above may further contain more than 0 atomic % and 1.5 atomic % or less of at least one element selected from the group consisting of Dy, Ho, and Er.
[25] The magnesium alloy according to any one of the above
[19] to
[23] may further contain Y in an amount of more than 0 atomic % and not more than 1.0 atomic %.
[26] The magnesium alloy according to any one of
[19] to
[25] above may further contain less than 3 atomic % in total of at least one element selected from the group consisting of Gd, Tb, Tm and Lu.
[27] The magnesium alloy according to any one of
[19] to
[26] above may further contain more than 0 atomic % and not more than 2.5 atomic % in total of at least one element selected from the group consisting of Al, Th, Ca, Si, Mn, Zr, Ti, Hf, Nb, Ag, Sr, Sc, B, and C.
[28] At least a part of the long period stacking ordered structure phase of the magnesium alloy according to any one of the above
[19] to
[27] may be curved or bent.
[29] A magnesium alloy comprising a total of a atomic % of at least one metal selected from the group consisting of Cu, Ni, and Co, a total of b atomic % of at least one element selected from the group consisting of Y, Dy, Er, Ho, Gd, Tb, and Tm, and the balance consisting of Mg and unavoidable impurities, wherein a and b satisfy the following (Equations 61) to (Equations 63), and the alloy has a crystalline structure having an α-Mg phase or a long period stacking ordered structure phase. (Formula 61)0.2≦a≦10 (Formula 62)0.2≦b≦10 (Formula 63)2 / 3a-2 / 3
[30] The magnesium alloy according to the above
[29] may further contain c atomic % Zn, and the a and c may satisfy the following (Formula 64). (Formula 64)0.2 <a+c≦15
[31] In the above
[30] , it is preferable that a and c further satisfy the following (Equation 65). (Formula 65)c / a≦1 / 2
[32] The magnesium alloy according to any one of the above
[29] to
[31] may further contain at least one element selected from the group consisting of La, Ce, Pr, Nd, Sm, Eu, Yb, and Lu in a total amount of d atomic %, and the b and d may satisfy the following (Equation 66). (Formula 66)0.2 <b+d≦15
[33] In the above
[32] , it is preferable that b and d further satisfy the following (Equation 67). (Formula 67)d / b≦1 / 2
[34] The magnesium alloy according to any one of
[29] to
[33] above may further contain e atomic % in total of at least one element selected from the group consisting of Zr, Ti, Mn, Al, Ag, Sc, Sr, Ca, Si, Hf, Nb, B, C, Sn, Au, Ba, Ge, Bi, Ga, In, Ir, Li, Pd, Sb, V, Fe, Cr, and Mo, where e satisfies the following (Formula 68): (Formula 68)0 <e≦2.5
[35] In the above
[34] , it is preferable that e, a, b, and d further satisfy the following (Equation 69). (Formula 69)e / (a+b+c+d)≦1 / 2
[36] The magnesium alloy may be an alloy containing a atomic % Zn, a total of b atomic % of at least one element selected from the group consisting of Y, Dy, Ho, and Er, a total of c atomic % of at least one element selected from the group consisting of La, Ce, Pr, Nd, Sm, Gd, Tb, and Yb, with the balance being Mg and unavoidable impurities, wherein a, b, and c satisfy the following (Equations 71) to (Equations 74), and the alloy has a crystalline structure having an α-Mg phase or a long period stacking ordered structure phase. (Formula 71)0.2≦a≦5.0 (Formula 72)0.2≦b≦5.0 (Formula 73)2a-3≦b (Equation 74) 0.05b≦c<0.75b
[37] The magnesium alloy described in the above
[36] may further contain d atomic % of Al and satisfy the following (Formula 75): (Formula 75) 0.05b≦d<0.75b
[38] The magnesium alloy according to the above
[36] or
[37] may contain at least two of the elements Y, Dy, Ho and Er in a total of b atomic %.
[39] The magnesium alloy may be an alloy containing a atomic % of Zn, a total of b atomic % of at least one of Gd and Tb, a total of c atomic % of at least one element selected from the group consisting of Al, Y, La, Ce, Pr, Nd, Sm, Dy, Ho, Er, Tm, and Yb, with the balance being Mg and unavoidable impurities, wherein a, b, and c satisfy the following (Formula 81) to (Formula 84), and the alloy has a crystal structure having an α-Mg phase or a long period stacking ordered structure phase. (Formula 81)0.2≦a≦5.0 (Formula 82)0.2≦b≦5.0 (Formula 83)2a-3≦b (Equation 84) 0.05b≦c<0.75b
[40] The magnesium alloy may be an alloy containing a atomic % of Al, b atomic % of Gd, and the remainder being Mg and unavoidable impurities, where a and b satisfy the following (Equation 91) and (Equation 92), and the alloy has a crystal structure having an α-Mg phase, a long period stacking ordered structure phase, or a phase containing close-packed atomic area stacking faults. (Formula 91)0.01≦a≦2.0 (Formula 92)0.2≦b≦5.0 In this specification, the term "close-packed atomic surface stacking defect" refers to a case in which solute atoms, zinc and a rare earth element, are concentrated in two consecutive atomic layers in the stacking direction along a close-packed atomic surface (solute-atom-enriched diatomic layer), and the solute-atom-enriched diatomic layer does not have periodicity in the stacking direction over a long distance.
[41] The magnesium alloy may be an alloy containing a atomic % Zn, a total of b atomic % of at least one element selected from the group consisting of Y, Dy, Ho, Er, Gd, Tb, and Tm, c atomic % Al, and the balance being Mg and unavoidable impurities, wherein a, b, and c satisfy the following (Equations 101) to (Equations 104), and the alloy has a crystal structure having an α-Mg phase, a long period stacking ordered structure phase, or a phase containing close-packed atomic area stacking faults. (Formula 101)0.2≦a≦5.0 (Formula 102)0.2≦b≦5.0 (Formula 103)2a-3≦b (Equation 104) 0.05b≦c<0.75b
[42] The magnesium alloy according to
[41] above may further contain d atomic % in total of at least one element selected from the group consisting of Li, Sn, Di, La, Ce, Pr, Nd, Sm, Eu, Mm, Yb, Th, Ca, Si, Mn, Zr, Ti, Hf, Nb, Ag, Sr, Sc, B, C, Ga, and Ge, where d satisfies the following (Formula 105): (Formula 105)0≦d≦b / 2
[43] The magnesium alloy may have any one of the chemical components listed below in (A) to (G). (A) By mass%, Al: 0.1 to 12.0%, Mn: 0.1 to 1.0%, and the remainder being Mg and impurities (B) In terms of mass%, it contains Al: 0.1-12.0%, Mn: 0.1-1.0%, and further contains one or more elements selected from Zn: 0.5-2.0%, Si: 0.3-2.0%, and the balance is Mg and impurities. (C) By mass%, Zn: 1.0 to 10.0%, Zr: 0.4 to 2.0%, and the balance being Mg and impurities (D) By mass%, Zn: 1.0-10.0%, Zr: 0.4-2.0%, Mn: 0.5-2.0%, and the remainder being Mg and impurities. (E) By mass%, Zn: 1.0 to 10.0%, rare earth elements: 1.0 to 3.0%, and the balance being Mg and impurities (F) By mass%, Zr: 0.4 to 2.0%, rare earth elements: 1.0 to 3.0%, and the remainder being Mg and impurities. (G) By mass%, Zn: 1.0-10.0%, Mn: 0.1-1.0, Cu: 0.5- 2.0%, the balance being Mg and impurities
[44] The magnesium alloy may contain a atomic % of Zn and b atomic % of Y, where a and b satisfy the following (Formula 11) to (Formula 13) or (Formula 14) to (Formula 16), and may be an alloy having a crystalline structure having an α-Mg phase or a long period stacking ordered structure phase. (Formula 11) 0.25≦a<5.0 (Formula 12)0.5 <b<5.0 (Formula 13)2 / 3a-5 / 6≦b (Formula 14)0.25≦a≦5.0 (Formula 15)0.5≦b≦5.0 (Formula 16)0.5a≦b
[45] The magnesium alloy may contain a atomic % of Zn and a total of b atomic % of at least one element selected from the group consisting of Dy, Ho, and Er, where a and b satisfy the following (Equations 21) to (Equation 23) or (Equations 24) to (Equations 26), and have a crystalline structure having an α-Mg phase or a long period stacking ordered structure phase. (Formula 21)0.1≦a≦5.0 (Formula 22)0.1≦b≦5.0 (Formula 23)0.5a-0.5≦b (Formula 24)0.1≦a≦3.0 (Formula 25)0.1≦b≦5.0 (Formula 26)2a-3≦b
[46] The magnesium alloy may contain a atomic % of Zn and a total of b atomic % of at least one element selected from the group consisting of Gd, Tb, Tm, and Lu, where a and b satisfy the following (Formula 41) to (Formula 43) or (Formula 44) to (Formula 46), and have a crystalline structure having an α-Mg phase or a long period stacking ordered structure phase. (Formula 41)0.1≦a≦5.0 (Formula 42)0.25≦b≦5.0 (Formula 43)0.5a-0.5≦b (Formula 44)0.1≦a≦3.0 (Formula 45)0.25≦b≦5.0 (Formula 46)2a-3≦b
[47] The magnesium alloy may comprise a total of a atomic % of at least one metal selected from the group consisting of Cu, Ni, and Co, and a total of b atomic % of at least one element selected from the group consisting of Y, Dy, Er, Ho, Gd, Tb, and Tm, where a and b satisfy the following (Formula 61) to (Formula 63), and have a crystalline structure having an α-Mg phase or a long period stacking ordered structure phase. (Formula 61)0.2≦a≦10 (Formula 62)0.2≦b≦10 (Formula 63)2 / 3a-2 / 3
[48] The magnesium alloy may comprise an alloy containing a atomic % of Al and b atomic % of Gd, where a and b satisfy the following (Eqs. 91) and (Eq. 92), and having a crystalline structure containing an α-Mg phase or a long period stacking ordered structure phase. (Formula 91)0.01≦a≦2.0 (Formula 92)0.2≦b≦5.0
[0037] (Embodiment 4) A method for producing a stent according to one embodiment of the present invention will be described. The stent is a stent for cerebral aneurysm shown in FIG.
[0038] <Wire rod manufacturing method> First, a magnesium alloy base wire having a small average crystal grain size of the α-Mg phase is prepared. Specifically, a molten magnesium alloy containing 90 atomic % or more of Mg is rapidly solidified to produce a plurality of rapidly solidified products. The cooling rate is preferably faster than 1000 K / sec (preferably 10000 K / sec). The plurality of rapidly solidified products are, for example, powder produced by the RS-P / M method (or flakes, ribbons or thin wires produced by the RS-P / M method, or thin wires produced by the molten metal extraction method).
[0039] Next, the multiple rapidly solidified products are hot extruded to produce a solidified molded product. In detail, the powder (or flakes, ribbons, or thin wires) is filled into a copper can and vacuum sealed to produce a billet, which is then extruded to produce a solidified molded product. Another method of solidifying the powder is to roll the powder using a grooved roll.
[0040] It is preferable that the inner surface of the copper can be chrome-coated (e.g., Cr-plated). This can prevent copper from diffusing into the magnesium alloy, thereby improving the corrosion resistance of the wire to be produced. In other words, if the magnesium alloy contains about 100 ppm of copper, the corrosion resistance will be deteriorated, but by coating the inner surface of the copper can with chrome, it is possible to prevent copper from diffusing into the magnesium alloy, thereby obtaining the inherent corrosion resistance of the magnesium alloy.
[0041] Next, the solidified product is extruded to produce a magnesium alloy base material wire having a small average crystal grain size of the α-Mg phase. In this embodiment, the magnesium alloy base wire having a small average crystal grain size of the α-Mg phase is produced by the rapid solidification powder metallurgy (RS-P / M) method, but the magnesium alloy base wire having a small average crystal grain size of the α-Mg phase may also be produced from a magnesium alloy billet produced by a casting method by a method that imparts large strain to the material, such as the equal-channel-angular-extrusion (ECAE) processing method.
[0042] The ECAE processing method is a method in which the longitudinal direction of the sample is rotated by 90° for each pass in order to introduce uniform strain into the sample. Specifically, the ECAE processing method is a method in which a magnesium alloy casting, which is a molding material, is forced into a molding hole having an L-shaped cross section of a molding die, and stress is applied to the magnesium alloy casting, particularly at the 90° bent portion of the L-shaped molding hole, to obtain a molded body. The number of passes of the ECAE is preferably multiple. The processing temperature during the ECAE processing is preferably, for example, 250°C to 500°C.
[0043] After the above-mentioned magnesium alloy base wire is produced, the magnesium alloy base wire is subjected to multiple drawing processes to produce a magnesium alloy wire having an α-Mg phase. In this specification, the terms "magnesium alloy base wire" and "magnesium alloy wire" are defined as follows. The magnesium alloy wire means a wire after multiple drawing processes have been completed. The magnesium alloy base wire means a wire before multiple drawing processes and a wire in the middle of multiple drawing processes. In other words, the magnesium alloy base wire means all wires before multiple drawing processes are completed. For example, if the processing step shown in FIG. 8 is the final drawing process at the end of multiple drawing processes, the wire before the final drawing process becomes the magnesium alloy base wire 41, and the wire after the drawing process becomes the magnesium alloy wire 42. Also, if the processing step shown in FIG. 8 is a drawing process in the middle of multiple drawing processes, the wire before the intermediate drawing process becomes the magnesium alloy base wire 41, and the wire after the drawing process becomes the magnesium alloy base wire 42.
[0044] The above-mentioned magnesium alloy base wire is preferably formed from a magnesium alloy that does not (or is unlikely to) undergo grain growth when heat-treated at a temperature of 300°C, and may be a general-purpose magnesium alloy, an LPSO (Long-Period Stacking Ordered) type alloy, pure magnesium, etc., and may be formed from, for example, any of the alloys [1] to
[48] listed above.
[0045] As shown in Fig. 8, a magnesium alloy base material wire 41 having a wire diameter of, for example, more than 1 mm and less than 3 mm is drawn in the direction of the arrow using a die 43 at a drawing speed of 0.1 m / min to 1000 m / min (preferably 0.1 m / min to 100 m / min, more preferably 0.5 m / min to 100 m / min) to form a magnesium alloy wire (a magnesium alloy base material wire in the middle of multiple drawing processes) 42. The temperature of the magnesium alloy base material wire 41 during the drawing process (i.e., the temperature of the magnesium alloy base material wire 41 when passing through the die 43) is preferably in the range of room temperature to 450°C, or 150°C to 350°C, or more than 200°C to 300°C. The reason for setting such a temperature range is that the magnesium alloy base material wire is less likely to break during the drawing process and the temperature or time of heat treatment for removing distortion after the drawing process can be reduced. The reason for reducing the temperature or time of the heat treatment is that a small temperature or time can suppress the grain growth of the α-Mg phase.
[0046] In this specification, the wire diameter of the magnesium alloy base material wire means, for example, the wire diameter d3 of the magnesium alloy base material wire 41 shown in FIG. 8, and when the cross-sectional shape of the magnesium alloy base material wire is not circular, it means the maximum outer diameter of the cross section of the magnesium alloy base material wire.
[0047] When the magnesium alloy base material wire 41 at room temperature is subjected to the first drawing process, heat due to friction between the die 43 and the magnesium alloy base material wire 41 when passing through the die 43 is applied to the magnesium alloy base material wire 42 after drawing, and taking this into consideration, the temperature of the die 43 is controlled. For example, the temperature of the die 43 is controlled to be 200° C. or higher and 300° C. or lower. This makes it possible to keep the temperature of the magnesium alloy base material wire 41 in the above range when the drawing process is performed.
[0048] When performing the second drawing process, the temperature of the magnesium alloy base material wire 41 is returned to room temperature, and the magnesium alloy base material wire 41 at room temperature is passed through a die 43 whose temperature is controlled to perform the drawing process. This drawing process is repeated multiple times until the wire diameter D of the magnesium alloy wire 42 satisfies the following (Equation 41). The magnesium alloy wire 42 that satisfies the following (Equation 41) has an α-Mg phase, and when the average crystal grain size of the α-Mg phase observed in a cross section cut in the longitudinal direction of the magnesium alloy wire 42 is L (not shown), and the average crystal grain size of the α-Mg phase observed in a cross section cut in a direction perpendicular to the longitudinal direction is d (not shown), it is preferable that the following (Equations 42) and (43) are satisfied. (Formula 41) 5μm≦D≦50μm (Formula 42) d≦1 μm (preferably, d≦0.5 μm, more preferably, d≦0.3 μm, even more preferably, d≦0.19 μm, even more preferably, d≦0.12 μm, and even more preferably, d≦0.1 μm) (Formula 43) 10≦L / d (preferably 43≦L / d, more preferably 54≦L / d, even more preferably 70≦L / d, and even more preferably 90≦L / d)
[0049] When performing each of the above multiple drawing processes, it is advisable to supply non-silicon oil, such as edible oil, as a lubricant to the die 43. This can reduce frictional heat between the die 43 and the magnesium alloy base material wire 41, and can prevent the wire from breaking during the drawing process. The area reduction rate RA when performing each of the above-mentioned multiple drawing processes should satisfy the following formula (45), preferably the following formula (45'), and more preferably the following formula (45''). (Formula 45) 1%≦RA≦30% (Formula 45')3%≦RA≦15% (Formula 45'')5%≦RA≦12%
[0050] The reduction in area is calculated by the following formula: (1-(D / d3)) where d3 is the wire diameter before drawing and D is the wire diameter after drawing.2 ) × 100. Moreover, the wire diameter of the magnesium alloy base material wire 41 gradually decreases as the magnesium alloy base material wire 41 is subjected to multiple drawing processes. The magnesium alloy base material wire 42 after at least one of the multiple drawing processes is subjected to heat treatment. The temperature of this heat treatment is preferably 50°C higher than the temperature of the magnesium alloy base material wire 42 immediately after the drawing process immediately before the heat treatment and between 450°C and 450°C, or between 50°C higher than the temperature of the magnesium alloy base material wire 42 immediately after the drawing process immediately before the heat treatment and between 400°C and 10 seconds and 12 hours.
[0051] The timing for carrying out the heat treatment is when the average grain size of the α-Mg phase in the magnesium alloy base material wire 42 after multiple drawing processes becomes significantly smaller than the average grain size of the α-Mg phase in the magnesium alloy base material wire 41 before multiple drawing processes. The number of times for carrying out the heat treatment may be multiple, and may be adjusted as appropriate.
[0052] For example, the heat treatment may be performed after each drawing process, or the heat treatment may be performed after each drawing process and not after each drawing process. For example, if the heat treatment temperature is 350°C and the heat treatment time is 30 minutes, the formation of an oxide film on the surface of the magnesium alloy wire 42 can be reduced even if the heat treatment is performed in an air atmosphere. In other words, the formation of an oxide film is reduced even if the heat treatment is performed.
[0053] In this way, it is possible to manufacture magnesium alloy wire 42 having a wire diameter D of 5 μm or more and 100 μm or less, and an average crystal grain size d of the α-Mg phase of 1 μm or less (preferably 0.5 μm or less, more preferably 0.3 μm or less, and even more preferably 0.1 μm or less). In this case, it is preferable that the wire diameter D and the average crystal grain size d satisfy the following (Equation 44). (Formula 44) d / D≦1 / 100 (preferably 1.15 / 300 or less, more preferably 1.9 / 500 or less, even more preferably d / D≦1 / 300, more preferably d / D≦1 / 500)
[0054] The magnesium alloy wire 42 corresponds to the wire material of the first to third embodiments, and the Young's modulus (modulus of longitudinal elasticity) of this wire material is preferably 50 GPa or less.
[0055] The wire for producing a flow diverter stent has a wire diameter of 50 μm or less, preferably 30 μm or less, and the wire for producing a coil embolization stent has a wire diameter of 100 μm or less, preferably 80 μm or less. Furthermore, the yield stress (0.2% proof stress) of the magnesium alloy wire 42 obtained as described above is 300 MPa or more, preferably 400 MPa or more, more preferably 500 MPa or more, even more preferably 600 MPa or more, and even more preferably 700 MPa or more.
[0056] According to the above embodiment, the magnesium alloy base material wire 41 having a small crystal grain size is produced by the rapid solidification powder metallurgy method, and then the magnesium alloy base material wire 41 is repeatedly subjected to drawing and heat treatment processes so as to suppress recrystallization and grain growth as much as possible, thereby making it possible to make the average crystal grain size of the α-Mg phase 1 μm or less for a given wire diameter. This makes it possible to realize a magnesium alloy wire 42 having high strength or high corrosion resistance.
[0057] Furthermore, even if the wire diameter of the magnesium alloy wire 42 is thinned to 100 μm or less, 50 μm or less, or 30 μm or less, a wire that is difficult to break can be realized.
[0058] Next, the wire produced by the above method may be subjected to a surface treatment or coating in order to adjust the time period until the stent decomposes after placement in a blood vessel or the bioabsorption rate. As mentioned above, the required bioabsorption rate differs between a flow diverter stent and a coil embolization stent, and it is also considered that the required bioabsorption rate differs depending on the size and condition of the cerebral aneurysm.
[0059] Examples of surface treatments for wires include hydrofluoric acid treatment or anodizing. Oxides or fluorides are formed on the surface of the wire by surface treatments. Examples of coatings for wires include polymer bonding or polymer coating on the surface of the wire, or DLC film formation.
[0060] <Wire weaving process> Next, the wires are braided with a braider (braiding machine) at a number of 8 or more (preferably 16 or more) to produce the stent 10 consisting of a cylindrical braid as shown in FIG. 1. The braid is made by braiding the wires into a cylindrical shape by alternately crossing them. The twist of the wires during braiding is preferably 1 turn or less per 10 cm of wire length. To reduce the twist, the diameter of the braider's bobbin may be increased, or a vertical bobbin may be used.
[0061] Here, when producing the coil embolization stent 30, it is preferable to braid eight or more wires, and more preferably to braid 16 or more wires. Furthermore, when producing a flow diverter stent 20, it is preferable to braid 24 or more wires, and more preferably, 48 or more wires. In addition, it is preferable that the outer diameter of the stent formed from the above braid is constant over its entire length, and the density of the braid is uniform throughout.
[0062] Next, the stent braided by the above method may be subjected to a surface treatment or coating. In this case, it is better not to perform a surface treatment or coating on the wire material. By performing such a surface treatment or coating, it is possible to adjust the time period until the stent decomposes or the rate of bioabsorption after the stent is placed in the blood vessel.
[0063] Examples of surface treatments of stents include hydrofluoric acid treatment or anodizing treatment of the surface of the stent, which forms oxides or fluorides on the surface of the stent. Examples of coatings of stents include polymer bonding or polymer coating of the surface of the stent, or DLC film formation treatment.
[0064] Next, the stent may be heat-treated to fix the shape of the stent. The heat treatment conditions are preferably a temperature in the range of from room temperature to 400°C and a treatment time of 1 second to 12 hours. The stent shape during heat treatment is preferably larger than the diameter when placed in the blood vessel. This larger diameter is equal to the external shape after expansion, and the stent is stretched in the length direction when inserted. The order of the heat treatment of the stent and the surface treatment or coating of the stent may be reversed.
[0065] The above first to fourth embodiments can be implemented in appropriate combination with each other. EXAMPLES
[0066] FIG. 9 is a photograph (SEM photograph) showing the appearance of each of the wires of Sample 1, Sample 2, Sample 3, Sample 4, and Sample 5 according to Example 1.
[0067] Sample 1 is a magnesium alloy wire (wire rod) with a wire diameter of 95.5 μm obtained by solidifying and molding powder, flakes, ribbons, or thin wires produced by the RS-P / M method, extruding the solidified molded product, and then performing multiple drawing processes and heat treatments. The alloy composition is Mg 97.94 -Zn 0.56 -Y 1.5Sample 2 is a wire with a wire diameter of 73 μm obtained by further applying drawing and heat treatment to Sample 1 several times. Sample 3 is a wire with a wire diameter of 49.2 μm obtained by further applying drawing and heat treatment to Sample 2 several times. Sample 4 is a wire with a wire diameter of 32 μm obtained by further applying drawing and heat treatment to Sample 3 several times. Sample 5 is a wire with a wire diameter of 29.7 μm obtained by further applying drawing and heat treatment to Sample 4. The wire diameters of the wires were measured using a high-precision digital micrometer (MDH-25MB manufactured by Mitutoyo Corporation).
[0068] The magnesium alloy base material wire 41 is produced as follows. Mg 97.94 -Zn 0.56 -Y 1.5 The alloy was melted by gas heating in an argon gas atmosphere, and approximately 2 × 10 5 The alloy powder is produced by cooling at a cooling rate of 1000 K / sec. The alloy powder is then preformed at a pressure of 60 to 170 MPa and vacuum degassed at a temperature of 250°C for 2 hours to produce a billet. The die and container are then fixed, and the billet is pressed against the die to perform extrusion. The extrusion conditions are as follows: Extrusion speed: 2.5mm / min Container, die and billet temperature: 350℃ Extrusion ratio: 15
[0069] In this embodiment, the 5 The cooling rate is 1×10 5 K / sec or more 2×10 5 It is also possible to use cooling rates in the range of K / sec or less.
[0070] Sample 1 was prepared as follows. Temperature during drawing of magnesium alloy base material wire 41: 300°C for wire diameter of magnesium alloy base material wire 41 up to 1.08 mm, 225°C for wire diameters smaller than that Pulling speed: 0.1~1.0m / min Heat treatment temperature: 350℃ Heat treatment time: 10 minutes Frequency of heat treatment: For magnesium alloy base metal wire 41, with a wire diameter of up to 1.65 mm, heat treatment is performed after each drawing process. For wire diameters less than this, heat treatment is performed once for every two drawing processes. Die material: Magnesium alloy base material. Carbide dies are used for wire diameters up to 2.13 mm for wire 41, and diamond dies are used for wire diameters below that. Die temperature: 300℃ for wire diameters up to 1.08mm for magnesium alloy base wire 41, and 225℃ for wire diameters below that. Die lubricant: edible oil Pull-out direction: 2 directions Wire diameter of sample 1: 95.5μm
[0071] The drawing direction means the direction of the arrow shown in Fig. 8. The drawing direction having two directions means that when one direction is the direction of the arrow shown in Fig. 8, the other direction is a drawing direction in which the magnesium alloy base material wire 41 is rotated 180° and arranged in the opposite direction.
[0072] Sample 2 was prepared as follows. Temperature during drawing of magnesium alloy base wire 41: 225°C Pulling speed: 1.0m / min Heat treatment temperature: 350℃ Heat treatment time: 10 minutes Frequency of heat treatment: once every 2-4 processing steps Dice material: Diamond dice Die temperature: 225℃ Die lubricant: edible oil Pull-out direction: 2 directions Wire diameter of sample 2: 73μm Sample 3 was prepared as follows. Temperature during drawing of magnesium alloy base wire 41: 225°C Pulling speed: 1.0~5.0m / min Heat treatment temperature: 350℃ Heat treatment time: 10 minutes Frequency of heat treatment: once every 3 to 10 processing steps Dice material: Diamond dies Die temperature: 225℃ Die lubricant: edible oil Pull-out direction: 2 directions Wire diameter of sample 3: 49.2μm Sample 4 was prepared as follows. Temperature during drawing of magnesium alloy base wire 41: 225°C Pulling speed: 1.0~5.0m / min Heat treatment temperature: 350℃ Heat treatment time: 10 minutes Frequency of heat treatment: once for 12 or more processing steps Dice material: Diamond dies Die temperature: 225℃ Die lubricant: edible oil Pull-out direction: 2 directions Wire diameter of sample 4: 32μm Sample 5 was prepared as follows. Temperature during drawing of magnesium alloy base wire 41: 225°C Pulling speed: 1.0~5.0m / min Heat treatment temperature: 350℃ Heat treatment time: 10 minutes Frequency of heat treatment: once for 12 or more processing steps Dice material: Diamond dies Die temperature: 225℃ Die lubricant: edible oil Pull-out direction: 2 directions Wire diameter of sample 5: 29.7μm
[0073] FIG. 10 is a diagram showing the results of measuring the yield stress (0.2% proof stress) of each of the wires of Samples 1 to 5 shown in FIG. As shown in FIG. 10, the wire of Sample 1 has a yield stress of 467.9 MPa, the wire of Sample 2 has a yield stress of 482.1 MPa, the wire of Sample 3 has a yield stress of 515.7 MPa, the wire of Sample 4 has a yield stress of 622.0 MPa, and the wire of Sample 5 has a yield stress of 635.4 MPa.
[0074] FIG. 11 is a diagram showing the results of measuring the Young's modulus (modulus of longitudinal elasticity) of each of the wires of Samples 1 to 5 shown in FIG. As shown in FIG. 11, the wire of sample 1 has a Young's modulus of 42.8 GPa, the wire of sample 2 has a Young's modulus of 44.4 GPa, the wire of sample 3 has a Young's modulus of 45.1 GPa, the wire of sample 4 has a Young's modulus of 46.7 GPa, and the wire of sample 5 has a Young's modulus of 48.1 GPa. EXAMPLES
[0075] FIG. 12 is a photograph showing the appearance of the stent for cerebral aneurysm according to Example 2. A stent consisting of a tubular braid as shown in Figure 12 was produced by braiding 16 strands of wire (wire diameter: approximately 50 μm) of Sample 3 in Example 1 using a braider (braiding machine) for round cords (even number of strands).
[0076] According to Example 2, the outer diameter of the stent could be made constant over its entire length, and the braid density could also be made uniform overall. EXAMPLES
[0077] The sample of Example 3 was prepared as follows. Powder, flakes, ribbons, or wires produced by rapid solidification powder metallurgy were filled into a copper can and vacuum sealed to produce a billet, which was then extruded. The extruded product was then heat-treated at 738 K for 24 hours. The composition of the resulting magnesium alloy was Mg 97.25 -Zn0.75 The inner surface of the copper can used here is plated with Cr.
[0078] Comparative Example Sample 1 was prepared in the same manner as the above-mentioned Example 3 sample, except that the inner surface of the copper can was not plated with Cr. For comparative sample 2, an alloy of ASTM (USA) WE43 (magnesium alloy containing 4 mass% Y and 3 mass% rare earth elements) was cast, and the cast material was extruded as it was without being placed in a copper can. Therefore, copper was not diffused in comparative sample 2.
[0079] FIG. 13(A) is a graph showing the immersion time dependence of the corrosion rate in simulated body fluid for comparative samples 1 and 2, and FIG. 13(B) is a graph showing the immersion time dependence of the corrosion rate in simulated body fluid for the sample of Example 3 and comparative sample 1. The corrosion rate was measured by immersing the sample of Example 3 and the samples 1 and 2 of Comparative Examples in a simulated body fluid (HBSS: physiological balanced salt solution) adjusted to pH 7.4, and measuring the relationship between the immersion time and the corrosion rate. The simulated body fluid during the measurement was at a temperature of 310K and exposed to the atmosphere.
[0080] When magnesium contains about 100 ppm of Cu, its corrosion resistance deteriorates. In the case of sample 1 (comparative example) made using a copper can with no Cr plating on the inside, Cu diffuses into the billet material during extrusion, deteriorating its corrosion resistance. In contrast, the sample of Example 3, which was made using a copper can with Cr plating on the inside, prevents Cu from diffusing into the billet material during extrusion, and therefore has inherent corrosion resistance, and is therefore better than Sample 1 of the Comparative Example.
[0081] Furthermore, although Cu is not diffused into the comparative sample 2, the sample of the embodiment 3 has better corrosion resistance than the comparative sample 2. EXAMPLES
[0082] FIG. 15 is a photograph showing the appearance of the stent for cerebral aneurysm according to Example 4. A stent consisting of a tubular braid as shown in Figure 15 was produced by braiding 48 strands of wire (wire diameter: approximately 50 μm) of Sample 3 in Example 1 using a braider (braiding machine) for round cords (even number of strands).
[0083] According to Example 4, the outer diameter of the stent could be made constant over its entire length, and the braid density could also be made uniform overall. [Explanation of symbols]
[0084] 10. Stents for cerebral aneurysms 11a,11b,13,15,16,17a,17b...Wire rod 12,14,19…Stents for cerebral aneurysms 18...Angle formed by wire 11a and wire 11b 20...Flow diverter stent 21,31…Cerebral aneurysm 22,32…blood vessels 30…Coil embolization stent 33…Coil 41…Magnesium alloy base metal wire 42…Magnesium alloy wire 43…Dice d3: Magnesium alloy base metal wire diameter D: Magnesium alloy wire diameter
Claims
1. A method for manufacturing a stent that has self-expanding properties and is placed across a cerebral aneurysm by being pressed against a blood vessel wall, comprising: The method includes the step (a) of weaving a wire material with a number of strands of 8 or more, The wire is made of a magnesium alloy containing 90 atomic % or more of Mg or pure magnesium, and has a yield stress (0.2% proof stress) of 300 MPa or more and a Young's modulus (modulus of longitudinal elasticity) of 50 GPa or less, A method for producing a stent, wherein the diameter of the wire is 100 μm or less.
2. In claim 1, the stent is a flow diverter stent, The number of strokes is 24 or more, A method for producing a stent, wherein the wire has a diameter of 50 μm or less.
3. In claim 1 or 2, A method for manufacturing a stent, characterized in that it has a step (b) of applying a surface treatment or coating to the wire before the step (a), or has a step (c) of applying a surface treatment or coating to the stent after the step (a).
4. In claim 3, The step (b) is to perform a polymer bonding or polymer coating on the surface of the wire, or to perform a hydrofluoric acid treatment, an anodizing treatment, or a DLC film formation treatment on the surface of the wire; The method for manufacturing a stent, wherein the step (c) comprises subjecting the stent to a hydrofluoric acid treatment, an anodizing treatment, or a DLC film formation treatment.
5. In any one of claims 1 to 4, The method includes a step (d) of producing the wire before the step (a), The step (d) includes the steps of: (e) rapidly solidifying a molten magnesium alloy containing 90 atomic % or more of Mg or pure magnesium to produce a plurality of rapidly solidified products; (f) filling and sealing the plurality of rapidly solidified products in a copper can to produce a billet, and extruding the billet to produce a solidified product; (g) extruding the solidified product to produce a magnesium alloy base material wire; and (h) drawing the magnesium alloy base material wire a plurality of times to produce a magnesium alloy wire having an α-Mg phase or a long period stacking ordered structure phase, A method for manufacturing a stent, characterized in that the inner surface of the can is subjected to a chrome coating treatment.
Citation Information
Patent Citations
Vascular expandable devices
US20190240050A1
Magnesium-based biodegradable metal material
WO2007058276A1
Bioabsorbable medical device and method for producing same
WO2018083998A1
Flow diverter stent
JP2013135794A